In vitro bioactivity studies of ceramic structures isolated from marine sponges - Barros, Alexandre António Antunes (2016)
In this work, we focused on the potential of bioceramics from different marine spongesâ namely Petrosia ficiformis, Agelas oroides and Chondrosia reniformisâ for novel biomedical/industrial applications. The bioceramics from these sponges were obtained after calcination at 750 Â°C for 6 h in a furnace. The morphological characteristics were evaluated by scanning electron microscopy (SEM). The in vitro bioactivity of the bioceramics was evaluated in simulated body fluid (SBF) after 14 and 21 d. Observation of the bioceramics by SEM after immersion in SBF solution, coupled with spectroscopic elemental analysis (EDS), showed that the surface morphology was consistent with a calcium-phosphate (Ca/P) coating, similar to hydroxyapatite crystals (HA). Evaluation of the characteristic peaks of Ca/P crystals by Fourier transform infrared spectroscopy and x-ray diffraction further confirmed the existence of HA. Cytotoxicity studies were carried out with the different ceramics and these were compared with a commercially available BioglassÂ®. In vitro tests demonstrated that marine bioceramics from these sponges are non-cytotoxic and have the potential to be used as substitutes for synthetic BioglassÂ®.